2016
DOI: 10.1097/gme.0000000000000683
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing of FDA-approved and compounded hormone therapy differs by specialty

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The percentage of physicians who completed the survey could also be a limitation; while the number of completed surveys was not very high (27%), it was also not particularly low when compared with the completion rates other surveys (10%–41%) in the published medical literature. 18,21,22,24 In addition, the demographics of the respondents were fairly similar to the data of the 2016 Physician Specialty Data Report, which reported that males account for 46% of OB/GYNs and 62% of family medicine/general practice physicians in the United States, with the majority (56% and 58%, respectively) being under the age of 55. 51 Physicians who completed the survey also received an incentive, which could have affected how they answered the questions.…”
Section: Discussionsupporting
confidence: 67%
“…The percentage of physicians who completed the survey could also be a limitation; while the number of completed surveys was not very high (27%), it was also not particularly low when compared with the completion rates other surveys (10%–41%) in the published medical literature. 18,21,22,24 In addition, the demographics of the respondents were fairly similar to the data of the 2016 Physician Specialty Data Report, which reported that males account for 46% of OB/GYNs and 62% of family medicine/general practice physicians in the United States, with the majority (56% and 58%, respectively) being under the age of 55. 51 Physicians who completed the survey also received an incentive, which could have affected how they answered the questions.…”
Section: Discussionsupporting
confidence: 67%
“…1,2 The prevalence of GSM is reported to be as high as 50% to 70% [3][4][5][6][7] in postmenopausal women; however, according to a 2013 study, only 7% of affected women are being treated with prescription therapy. 2 Although previous surveys on the management and treatment for GSM have been undertaken in physician groups, [8][9][10] as well as separately evaluating nurse practitioners, 11 no surveys to date have examined differences in the evaluation and management of patients exhibiting GSM among healthcare providers (HCPs) in different specialties and training levels. Furthermore, HCPs in the Greater Memphis Area treat patients with high incidence rates of many comorbidities that serve as risk factors for GSM such as lack of exercise, 12 low education levels, 13 and morbid obesity.…”
mentioning
confidence: 99%
“…Menopausal hormonal therapy (MHT) ameliorates vasomotor symptomatology, prevents bone loss, and treats estrogen deficiency-related genitourinary symptoms [1]. As such, it is an FDA-approved therapy for these symptoms [1,2]. Whether MHT confers harmful or beneficial effects on cardiovascular (CV) system is controversial.…”
Section: Introductionmentioning
confidence: 99%